Correction: Adenosine A2A Receptor Up-Regulates Retinal Wave Frequency via Starburst Amacrine Cells in the Developing Rat Retina. - Pin-Chien Huang; Yu-Tien Hsiao; Shao-Yen Kao; Ching-Feng Chen; Yu-Chieh Chen; Chung-Wei Chiang; Chien-Fei Lee; Juu-Chin Lu; Yijuang Chern; Chih-Tien Wang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0095090.].